An integrated safety assessment method based on PSA and RAMI for fusion reactors. (March 2023) - Sun, Ming; Yu, Jie; Li, Taosheng; Ge, Daochuan
Highlights: PSA and RAMI were detailed compared. An integrated safety assessment method based on PSA and RAMI for fusion reactors was proposed. The case study of in-vessel LOCA accident for fusion reactors was performed to demonstrate the effectiveness of the proposed method. Abstract: Probabilistic Safety Assessment (PSA) is an important method to evaluate the safety concerns of Nuclear Power Plants (NPPs) from probability perspective. The Reliability, Availability, Maintainability, Inspectability (RAMI) approach was promoted by the International Thermonuclear Experimental Reactor (ITER) organization to evaluate system reliability and availability, and reduce the technical risks to an acceptable level from probability perspective for fusion devices. Both PSA and RAMI adopt probabilistic approach to evaluate the failure issues of nuclear systems. In this contribution, the analysis purposes, methods, objects, and quantitative analysis indexes of PSA and RAMI were firstly compared. Then, an integrated safety assessment method based on PSA and RAMI for fusion reactors was proposed, and the case study of in-vessel LOCA accident for fusion reactors was performed to demonstrate the effectiveness of the proposed method. The application results indicate that the proposed method not only can perform PSA, but also RAMI analysis for fusion reactors. The proposed method integrates the characteristics of PSA and RAMI, breaks the barrier between PSA and RAMI, preliminarily solves some problems of PSA for fusion reactors, and enriches the connotation of PSA for fusion reactors.